The effect of the smoothness of fractional type operators over their commutators with Lipschitz symbols on weighted spaces - Dalmasso, Estefanía Dafne (2018)
We prove boundedness results for integral operators of fractional type and their higher order commutators between weighted spaces, including Lp-Lq, Lp-BMO and Lp-Lipschitz estimates. The kernels of such operators satisfy certain size condition and a Lipschitz type regularity, and the symbol of the commutator belongs to a Lipschitz class. We also deal with commutators of fractional type operators with less regular kernels satisfying a Hörmander's type inequality. As far as we know, these last results are new even in the unweighted case. Moreover, we give a characterization result involving symbols of the commutators and continuity results for extreme values of p.